2019
DOI: 10.1038/s41598-019-49068-2
|View full text |Cite
|
Sign up to set email alerts
|

Cross-reactivity of sIgE to mite and shrimp induced allergies in different age groups and clinical profiles of shrimp sIgE in vegetarians

Abstract: The sensitization to house dust mites (HDMs) and shrimps affects the development of hypersensitivity with an increase in age. Due to the cross-reactivity between shellfish and HDMs, HDMs were considered as the primary sensitizer for shellfish allergy. Thus, vegetarians might be sensitized to shrimp through the inadvertent inhalation of HDMs. Therefore, we assessed the prevalence of shrimp or mite allergy among different age groups and vegetarians. The serum specific-IgE (sIgE) level of HDMs and shrimp in 60 ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Moreover, there seem to exist differences in mite–mollusc cross-reactivity depending on climate, a previous study revealed that TM and ubiquitin were responsible for mite–shellfish cross-reactivity from both continental dry and humid climates, while α-actinin and AK are involved in dry- and humid-climate groups, respectively . Shen et al indicated that environmental factors, lifestyles, and dietary habits play critical roles in allergen sensitization, IgE cross-reactivity to mite–shellfish-induced allergies and allergic disease development . As a result of the differences in geographical exposure to dust mite allergens and dietary variables, people living in different climatic zones may have different cross-reactive allergenic components of mite–mollusc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, there seem to exist differences in mite–mollusc cross-reactivity depending on climate, a previous study revealed that TM and ubiquitin were responsible for mite–shellfish cross-reactivity from both continental dry and humid climates, while α-actinin and AK are involved in dry- and humid-climate groups, respectively . Shen et al indicated that environmental factors, lifestyles, and dietary habits play critical roles in allergen sensitization, IgE cross-reactivity to mite–shellfish-induced allergies and allergic disease development . As a result of the differences in geographical exposure to dust mite allergens and dietary variables, people living in different climatic zones may have different cross-reactive allergenic components of mite–mollusc.…”
Section: Discussionmentioning
confidence: 99%
“…46 Shen et al indicated that environmental factors, lifestyles, and dietary habits play critical roles in allergen sensitization, IgE cross-reactivity to mite−shellfish-induced allergies and allergic disease development. 47 As a result of the differences in geographical exposure to dust mite allergens and dietary variables, people living in different climatic zones may have different cross-reactive allergenic components of mite− mollusc.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Immune cross-reactivity has been well documented between allergens (15)(16)(17)(18)(19), but it is unknown whether tolerogenic epitopes also display cross-reactivity. A computational search for homologous peptides revealed orthologs of the epitope recognized by the soy-specific TCR in the genomes of many other plants.…”
Section: Conservation Of Tcr Epitopes Across the Plant Kingdommentioning
confidence: 99%
“…Not surprisingly, it has been proposed that the immunological cross-reactivity between allergens from commonly analyzed sources and their helminth-protein orthologs contributes to allergic sensitization associated with the acute and early stages of helminthiasis [25,[27][28][29]. This cross-reactivity has been observed not only with helminth proteins, but also with other invertebrates, which increases the associated problems not only for respiratory allergies, but also for food allergies [30][31][32]. This fact has crucial impacts on allergy diagnosis, as was thoroughly shown by other authors, leading to false positive results in allergy tests [25,27,33].…”
Section: Introductionmentioning
confidence: 99%